Pengaruh Pengembangan Media Flipbook pada Mata Pelajaran PAI Terhadap Hasil Belajar Siswa - Rohmad (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2021)
The rapid development of technology requires teachers to always be creative and innovative. One way is to use media for learning. The development of learning media is important to meet the needs of participants in accordance with their development. Elementary school-age learners need a lot of innovation for meaningful learning. The purpose of this research and development is to explain the difference in improving student learning outcomes in PAI subjects by using flipbook media and not using flipbook media in grade V students of MI Islamiyah Bojonegoro. The method used in this research and development is the Research And Development (R&D) method by adopting the ADDIE development model with the following stages: Analysis, Design, Development, Implementation and Evaluation. The sample in this study was class V students of MI Islamiyah Bojonegoro. The instruments used are interviews, observations, questionnaires and tests. Product validation carried out in development are: material experts, design experts, learning experts, and field tests conducted on grade V students of MI Islamiyah Bojonegoro. The results of this research and development created a flipbook learning media product on Islamic religious education learning in class V MI Islamiyah Bojonegoro material History of Islamic Culture History of Ulul Azmi. The learning media products developed have proven feasible and effective to use. This is shown in the results of validation and field tests that have been carried out. Expert validation of the material gets a percentage of 85%. Validation from design experts gets a percentage of 84.4%. While validation from learning experts gets a percentage of 85%. Field trials get a percentage of 84.6% which is said to be interesting. Test the effectiveness of flipbook media obtained from the results of pre-test and post-test students who have been calculated using the paired sample t-test formula with a significant value result of 0.000 so that H0 is rejected, meaning that there is a difference between before and after using flipbook learning media.